2017
DOI: 10.3390/ma10020123
|View full text |Cite
|
Sign up to set email alerts
|

Steering the Properties of MoOx Hole Transporting Layers in OPVs and OLEDs: Interface Morphology vs. Electronic Structure

Abstract: The identification, fine-tuning, and process optimization of appropriate hole transporting layers (HTLs) for organic solar cells is indispensable for the production of efficient and sustainable functional devices. In this study, the optimization of a solution-processed molybdenum oxide (MoOx) layer fabricated from a combustion precursor is carried out via the introduction of zirconium and tin additives. The evaluation of the output characteristics of both organic photovoltaic (OPV) and organic light emitting d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The smallest band offset (1.13 eV) between the valence band edge of V 0.05 MoO x and P3HT HOMO level favored the hole transport due to having the lowest resistance among all V-MoO x films [ 111 ]. Marchal et al reported a decrease of 3 nm in the surface roughness of MoO x HTL by adding 0.5 mol% of Zr and Sn via a combustion chemical deposition method at low temperatures [ 112 ]. The Zr and Sn atoms also covered the surface defects of MoO x , forming a uniform and well-covered HTL film on the ITO electrode (see Figure 4 a).…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
See 1 more Smart Citation
“…The smallest band offset (1.13 eV) between the valence band edge of V 0.05 MoO x and P3HT HOMO level favored the hole transport due to having the lowest resistance among all V-MoO x films [ 111 ]. Marchal et al reported a decrease of 3 nm in the surface roughness of MoO x HTL by adding 0.5 mol% of Zr and Sn via a combustion chemical deposition method at low temperatures [ 112 ]. The Zr and Sn atoms also covered the surface defects of MoO x , forming a uniform and well-covered HTL film on the ITO electrode (see Figure 4 a).…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“… ( a ) AFM and SEM images of unmodified and modified MoOx HTL. Adapted with permission from [ 112 ]. ( b ) Energy levels of pristine and doped MoO 3 with a NiOx layer.…”
Section: Figures Schemes and Tablesmentioning
confidence: 99%
“…Therefore, to achieve high PE, γ should be high while U should be low. Due to the unfavorable energy barriers between different layers together with the fact that electrons are minor charges in organic materials, charges balance and transport are usually unsatisfactory [ 62 , 63 , 64 , 65 , 66 ]. Therefore, charges should be not only well balanced but also effectively transported.…”
Section: Parameters To Characterize Woledsmentioning
confidence: 99%
“…Orthorhombic MoO 3 is an n-type semiconductor with a wide band gap (about 3.2 eV) and a high relative permittivity [4]. Therefore, MoO 3 can be used, among others, in batteries, resistive random-access memories, sensors, and organic light-emitting diodes [4][5][6][7][8][9][10][11][12]. An additional important aspect of MoO 3 is its layered structure, i.e., its adjacent two-dimensional (2D) crystalline layers are bound by weak van der Waals interactions [2,13].…”
Section: Introductionmentioning
confidence: 99%